Education And Production Of Herbal Drinks As Immune Booster For Students Of Senior High School 2 Medan - Cindylawsa, Gratia Apulina (INSTITUT KESEHATAN DELI HUSADA, 2025)
Traditional plants such as turmeric, temulawak, and ginger have been widely used by communities since ancient times as traditional drinks to treat illnesses and have been passed down to the present day. In addition to these main ingredients, other ingredients can also be added to enhance the flavor and provide an appetizing aroma, such as cinnamon, lemongrass, and sugar. These plants are rich in antioxidants that can boost the immune system. This article is the result of educating and making herbal drinks as immune boosters for 35 students in grade XI at SMA Negeri 2 Medan. Educating students and making herbal drinks as immune boosters is an effort to introduce the next generation to the many types of herbal plants in Indonesia that can be used to boost immunity. The outreach method was carried out in three stages, namely conducting a location survey, planning the outreach training preparations, and making herbal drinks. The outcome of the Community Service activity is to enhance students' understanding of the use of herbal plants as beverages that are beneficial for boosting the immune system.